2009
DOI: 10.4110/in.2009.9.4.133
|View full text |Cite
|
Sign up to set email alerts
|

Further Characterization of Activin A-induced IgA Response in Murine B Lymphocytes

Abstract: We have recently shown that activin A, a member of TGF-β superfamily, stimulates mouse B cells to express IgA isotype but other isotypes. In the present study, we further characterized effects of activin A on B cell growth and IgA expression. We found that activin A did not have effect on LPS-stimulated cell viability. In parallel, CFSE staining analysis revealed that activin A did not alter cell division. An increase of IgA secretion by activin A was completely abrogated by anti-activin A Ab but not by anti-T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…The effects of activin-A neutralization during allergic responses were observed even in the presence of endogenous TGF-b 1 , suggesting that these two cytokines, as also shown in other studies, should not be considered as redundant during inflammatory processes [24,25,27,28,42,44,45,53,60,62,63,65]. In support, activin-A and TGF-b 1 induce different Treg subsets, indicating that, at least in the Th2 setting, these factors operate through distinct suppressive mechanisms.…”
Section: Activin-a In the Regulation Of Experimental Asthmasupporting
confidence: 69%
See 1 more Smart Citation
“…The effects of activin-A neutralization during allergic responses were observed even in the presence of endogenous TGF-b 1 , suggesting that these two cytokines, as also shown in other studies, should not be considered as redundant during inflammatory processes [24,25,27,28,42,44,45,53,60,62,63,65]. In support, activin-A and TGF-b 1 induce different Treg subsets, indicating that, at least in the Th2 setting, these factors operate through distinct suppressive mechanisms.…”
Section: Activin-a In the Regulation Of Experimental Asthmasupporting
confidence: 69%
“…In addition, r-activin-A inhibits IL-6-driven mouse B cell proliferation and monocyte phagocytosis in vitro [27,52]. Activin-A increases IgA production from mouse mesenteric lymph node cells, pointing to a role for this cytokine in the maintenance of intestinal immune homeostasis [53]. In humans, in vitro studies have demonstrated that treatment of peripheral blood DCs with follistatin considerably enhances CD40Linduced pro-inflammatory cytokine and chemokine release, as well as, DC-driven CD8 1 T cell proliferation and IFN-g production [24].…”
Section: Anti-inflammatory Effectsmentioning
confidence: 99%
“…These data demonstrate that ActA is not an OCL survival factor, but when administered in combination with RANKL, ActA significantly inhibits RANKL-induced OCL maturation, survival and fusion. Given that ActA has been shown to regulate the lifespan of other hematopoietic cell types (Lee and Kim, 2009;Valderrama-Carvajal et al, 2002), the specific effects of ActA on the survival of mature OCL and their precursors was also examined.…”
Section: Discussionmentioning
confidence: 99%
“…25 In addition, an alternative mechanism for the induction of activin A by human bone marrow monocytes is through the cognate interaction with activated T cells requiring the CD40-CD40L interaction and T-cell-derived cytokines such as GM-CSF and interferon-g (IFN-g). 29 Mo-DCs and peripheral CD1c + myeloid DCs CD40L and agonists for TLR4 (LPS), -3 (poly-I:C) and -7/8 (R848) m activin A 72 A m IL-10, TNF-a, IL-6 and IL-12p70, MCP-1, RANTES, IL-8 and IP-10 84,85 B9 and MPC-11 cell lines Activin A promotes apoptosis 82 Splenic B cells and CH12F3-2 B-cell lymphoma Activin A sensitizes resting B cells to produce IgG after LPS activation [86][87][88] Activin A m IgA production induced by LPS…”
Section: Monocytesmentioning
confidence: 99%
“…More specifically, activin A enhanced IgA expression induced by LPS, and this effect appeared to be mediated by the induction of GLT a (Ig germline a) and PST a (post-switch transcripts a) in B-lymphoma cells and normal mouse-spleen B cells (Figure 3b). 87,88 Thus, activin A released by activated B cells has been proposed to regulate the antibody isotype switching in the spleen, acting on resting B cells, which, once activated, show upregulation of IgG isotype antibodies and, in this way, participate in the fine tuning of humoral responses. So far, it is unknown whether the expression and signaling of activin A can be regulated directly by the B-cell receptor as a possible crosstalk between both pathways.…”
Section: Role Of Activins/inhibins On Adaptive Immune Cells B Cellsmentioning
confidence: 99%